A produção de identidades profissionais no cenário musical de Santa Maria - Alvares, Felipe Batistella (2012)
This research has analyzed the processes of production of identities and subjectivities of the professional musician of Santa Maria, RS. It was done by questioning the discourses and the signification nets that are produced in and for the musical scene of Santa Maria. Inserted at the theorizations proposed by the Cultural Studies in Education, an investigation about this musical scene has been done, considering it as a pedagogical instance, which produces and rules behaviors, attitudes and ways of being a musician. Experiencing with a group of six professional musicians of the city, and also a set of documents which suggest the curricular directives of music courses, so as the pedagogicpolitical proposes of Federal University of Santa Maria and of REUNI governmental program, this task s objective was to understand the different ways by which the Santa Maria s musician individual is built, learning by working, learning inside the university and in so many other instances. The research itself was configured on the condition of possibilities for the emerging of three categories of analysis which served as basis for the analysis of this dissertation. The study tried to understand the symbolical productions between the discursive nets entitled as school of life and job market . A proposition of the task was to understand the circularity of these discourses, their strategies and negotiations on behalf of the musicians identity production. To guide this methodological path this investigation used an approach of ethnographical inspiration, which makes itself appropriate by allowing the researcher s professional condition to be legitimated as part of the explorations of the research, given that it was based on the Cultural Studies perspective. Keywords: cultural studies; education; culture; musical education.